PENGARUH MINAT BELAJAR PADA PEMAHAMAN AKUNTANSI DENGAN KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL SEBAGAI PEMODERASI - Atmaja, Rosko; Ramantha, I Wayan; Suartana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.05.TAHUN 2017, 2017)
This research has purpose to find out the influence of study interest to accounting comprehension to college students, to find out the influence of emotional intelligence that strengthen the influence of study interest to accounting comprehension to college students and to find out the influence of the spiritual intelligence that strengthen the influence of study interest to accounting comprehension to college students.  The independent variable in this research is the study interest, whereas the dependent variable used in this research is the accounting comprehension with emotional intelligence and spiritual intelligence as the moderation variable.  Data collection used the questionnaire with variable measurement of Likert scale.  Amount of sample used is 41 respondents.  The analysis technique used the interaction test by using moderated regression analysis data analysis technique.  Testing result shows that the study interest has positive influence to accounting comprehension.  The emotional intelligence strengthens the influence of study interest to accounting comprehension.  The spiritual intelligence strengthens the influence of study interest to accounting comprehension.
Keywords: Learning Interest, Emotional Intelegency, Spiritual Intelegency, Accounting Understanding